Stoichiometric Ecotoxicology for a Multisubstance World. (20th January 2021) - Peace, Angela; Frost, Paul C; Wagner, Nicole D; Danger, Michael; Accolla, Chiara; Antczak, Philipp; Brooks, Bryan W; Costello, David M; Everett, Rebecca A; Flores, Kevin B; Heggerud, Christopher M; Karimi, Roxanne; et al.
Abstract: Nutritional and contaminant stressors influence organismal physiology, trophic interactions, community structure, and ecosystem-level processes; however, the interactions between toxicity and elemental imbalance in food resources have been examined in only a few ecotoxicity studies. Integrating well-developed ecological theories that cross all levels of biological organization can enhance our understanding of ecotoxicology. In the present article, we underline the opportunity to couple concepts and approaches used in the theory of ecological stoichiometry (ES) to ask ecotoxicological questions and introduce stoichiometric ecotoxicology, a subfield in ecology that examines how contaminant stress, nutrient supply, and elemental constraints interact throughout all levels of biological organization. This conceptual framework unifying ecotoxicology with ES offers potential for both empirical and theoretical studies to deepen our mechanistic understanding of the adverse outcomes of chemicals across ecological scales and improve the predictive powers of ecotoxicology.